Cyclotomic Polynomials and Some Application - OUALID, Farida (Faculty of Mathematics and computer sciences Departement of Mathematics - Option : Algebra and Discrete mathematics, 2020)
In this memory, we have viewed the concepte of cyclotomic polynddomails. We have managed to study some of its propert ies, specifially focusing on their irreducibility and how dddthey relate to primes. Moreover, we have presented sdome applications of cyclotomic polynomials the most impddortant, Dirichlet’s theorem on primes in arithmetic progressions and Wedderburn’s little theorem .
Keywords: Cyclotomic Polynomials. Arithmetic progressions